PEMBERDAYAAN DAN PENGEMBANGAN AGROWISATA LEBAHMADU TRIGONA DALAM MENDUKUNG PENGEMBANGAN GEOPARK BELITUNG - Pranit, Diaz; Musthofa, Budiman Mahmud (UI Scholars Hub, 2021)
Belitung Island was declared a national geopark in 2016, and through UNESCO’s several sessions and process, finally granted UNESCO recognition as a member of UNESCO Global Geopark Networks in 2021. The local government and the people of East Belitung as part of the Belitung Geopark area, must have various creative programs for natural and cultural preservation while at the same time improve local welfare. One of the community initiatives that was successfully developed as a synergy for the preservation and welfare improvement approach in the context of geopark development is the cultivation of Trigona honey bees as an agro-tourism attraction. This study discusses the synergy of empowerment and development of agro-tourism as one of the preferred attractions of the Belitung Geopark. This study used a qualitative methodology and data were collected through observation, interviews and focus group discussions. The results showed that community involvement in Trigona honey cultivation originated from the initiative of local leaders as agents of change. Community participation in Trigona honey cultivation strongly supports environmental sustainability because the principle in Trigona honey bee cultivation must preserve the forest. The development of agro-tourism becomes an added value of Trigona honey cultivation which support the basic idea of the development of Belitung Geopark. This local initiative approach is closely related to sustainable tourism development includes 3P (people, planet, prosperity). Theoretically, this research contributes to the idea of a local initiative (local champion), which is able to mobilize and provide added value in the management of local resources to support geopark development.